Ionospheric Equatorial Plasma Bubble effects on L1 single frequency code GPS positioning using precise ephemerides - Clodoaldo De, S. F.; Moraes, Alison; Vani, Bruno C.; Costa, Emanoel; Monico, Joao F. Galera [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Amplitude and phase variations of Global Navigation Satellite Systems (GNSS) radio signals used by the aeronautic community occur due to ionospheric irregularities (ionospheric scintillation), which may cause the degradation of service availability and performance, raising safety issues. This is particularly true in the Appleton Anomaly region, where the occurrence of ionospheric irregularities is known to be frequent. In this work, the results from an analysis of the impact of ionospheric irregularities on the single point positioning performance of GPS is presented and discussed. The results show that the developed model has a good positioning measurements and few discrepancies. However, in the presence of ionospheric scintillation, degradations of positioning quality are observed. These promising results can be applied to data from other stations and positioning system, with the objective of directly characterizing ionospheric scintillation effects.
Keywords: availability; ionospheric scintillation; PPS